A Novel Treatment for Massive Hemorrhage after Maternal Trauma in Pregnancy - Gonzalez, Maritza G.; Wei, Ruth M.; Hatch, Kenneth D.; Gries, Lynn M.; Hill, Meghan G. (American Journal of Perinatology Reports, 2019)
Background Trauma in pregnancy can lead to life-threatening hemorrhage. Conventional treatments of hemorrhage include medical and surgical management. However, if these measures fail uterine compression is an option to control bleeding. We present a case where this management was employed.Case A patient presented at 36 weeks of gestation with multiple injuries after a motor vehicle collision and experienced disseminated intravascular coagulation (DIC). The use of a Bakri balloon in combination with external compression with Coban, a sterile self-adherent bandage, after delivery temporized her bleeding and allowed her to become stable for further management.Conclusion When other measures fail and a hysterectomy is considered unsafe, the combination of internal and external uterine compression is an option.
Keywords: trauma; pregnancy; uterine compression; disseminated intravascular coagulation